The evolution and significance of embolization efficiency index (EEI) during transcatheter hepatic arterial embolization procedure: a pilot study based on computational fluid dynamics - Wang, Zi-Xuan; Zhao, Yi-Fan; Qi, Quan (Frontiers in Bioengineering and Biotechnology, 2025)
PurposeTo investigate the hemodynamic determinants of the embolization efficiency index (EEI) during transcatheter hepatic arterial embolization (TAE), with the goal of improving embolization protocols, optimizing therapeutic precision, and mitigating the risks of non-target embolization.MethodsUsing computational fluid dynamics and patient-specific right hepatic artery geometry from cone-beam CT angiography, we evaluated the impact of inlet flow rate, target outlet pressure, and vascular hierarchy on EEI. Simulations in OpenFOAM solved Navier-Stokes equations under steady and pulsatile flow.ResultsThere was no correlation between inlet flow rate and EEI. Instead, EEI exhibited an inverse linear relationship with target pressure, declining until flow cessation at a certain pressure greater than 5000Pa. Proximity to the target outlet significantly enhanced EEI. Backflow phenomenon indicated inherent non-target embolization risks under pulsatile conditions.ConclusionThis proof-of-concept study suggests that, in this model, EEI is primarily influenced by outlet pressure and vascular anatomy, rather than inflow dynamics. These findings call into question the conventional emphasis on flow modulation, pointing to the potential value of pressure-aware strategies and superselective catheter placement near targets. Based on the analyzed case, the study offers quantitative thresholds and spatial EEI gradients that could help refine TAE precision and potentially reduce complications. With further validation, integrating such CFD-based EEI metrics into procedural planning may contribute to standardizing embolization protocols.